Ethics of Care as Practical Theology and the Autonomous Sphere for Muslim Women in Gender Jihad - Ilzam Hubby Dzikrillah Alfani (Fikr: Jurnal Pemikiran Studi Islam, 2026)
This article analyzes the concept of the ethics of care within Amina Wadud's thought, not as an abstract ethical theory, but as a manifestation of practical theology that shapes spaces of autonomy and agency for Muslim women. Focusing on the practices of grassroots movements such as Muslim Women United (MWU) and Together Righteousness Unites The Hearts (T.R.U.T.H.), this study argues that the care work they perform constitutes a concrete form of Gender Jihad a transformative struggle for gender justice. This practice reconstitutes the central Islamic concept of mu’amalat (just social relations), while also functioning as a tacit corrective to the failure of patriarchal Islamic structures in realizing social justice. The article demonstrates how the ethics of care builds legitimacy through impactful praxis, creates an alternative epistemology grounded in women's lived experiences, and offers a relational, justice-centered, and sustainable paradigm of Islam. These findings underscore the importance of reading theology not only from texts but also from the bodies and actions of women in everyday spaces.